2013
DOI: 10.4103/0973-8258.120211
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary phytochemical, toxicity and anti-inflammatory evaluation of Commelina benghalensis

Abstract: Background: Commelina benghalensis is a widely used ethno medicinal plant for various diseases in India, but only few studies have been conducted in this plant. Objective: The present work was performed to screen phytochemical, toxicity and anti-inflammatory activity of hydroethanolic extract of leaves of C. benghalensis (Family: Commelinaceae). Materials and Methods: Hydroethanolic extract of leaves of C. benghalensis (HECB) was prepared and subjected to preliminary phytochemical investigations. Acute and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Phytochemical examinations of aerial parts extracts revealed the presence of saponin, tannins, flavonoid, glycosides and phytosterols. These results have been established by Augustine et al (2013) and Tadesse et al (2016). The phytoconstituent rich ethanolic extract was elucidated using GC-MS as one of the best techniques which allows simultaneous assessment of a variety of components in the plant (Hussain and Maqbool, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Phytochemical examinations of aerial parts extracts revealed the presence of saponin, tannins, flavonoid, glycosides and phytosterols. These results have been established by Augustine et al (2013) and Tadesse et al (2016). The phytoconstituent rich ethanolic extract was elucidated using GC-MS as one of the best techniques which allows simultaneous assessment of a variety of components in the plant (Hussain and Maqbool, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies on chemical investigation of C.benghalensis by GC-MS revealed the presence of fourteen different compounds; the most investigated compounds were belonging to acid group. Others suggested that this plant was a potential source of 10 pharmacologically active chemical compounds and therefore investigate its antifungal, antimicrobial and antiinflammatory activity (Cuéllar Cuéllar and Okori, 2010;Augustine et al, 2013;Kadam, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Commelina benghalensis extract significantly decreased xylene-induced ear edema at doses of 200 mg/kg and 400 mg/kg. This indicates the anti-phlogistic and substance P inhibition properties of Commelina extracts [ 47 ].…”
Section: Pharmacological (Biological) Activities Of the Genus ...mentioning
confidence: 95%
“…A similar result to this study was reported by , who observed that the extract of Justicia secunda was well tolerated in mice as no signs of toxicity or death were noticed at 2 g/kg during the period under review. Tiwari et al (2013) attributed the toxicity, or otherwise, of an extract to the concentration or dose used in a system. Adeneye et al (2006) noted that the aqueous extract of Musanga cecropioides at a higher dose of 3000 mg/kg, was relatively safe toxicologically when administered orally.…”
Section: Effect Of the Leaf Extract On Enzyme Activitymentioning
confidence: 99%